Pengaruh Label Halal, Kualitas Produk, dan Harga terhadap Keputusan Pembelian Produk Minuman Sari Apel - Alfiyatul Fitriyah (Jurnal Ilmiah Ekonomi Islam, 2023)
This study intends to ascertain the impact of the halal label, product quality, and price on purchase decisions for apple cider goods in Andonosari Village in part and concurrently. This study is quantitative in nature. The instrument test, traditional assumption test, multiple linear regression test, and hypothesis testing are the methods used to assess the hypothesis. In this study, 52 respondents made up the sample. The major data utilized were those from customer surveys on apple cider products in Andonosari Village. The findings demonstrated that the Andonosari Village consumers' decisions to purchase apple cider products were influenced both partially and concurrently by the halal label, product quality, and price. According to the study on this hypothesis, price, product quality, and the halal label all have positive and substantial effects on buying choices. They also all have a positive and significant impact on the quality of the product.